2019
DOI: 10.1096/fj.201802711r
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a involved in the mechanical loading on improvement of bone remodeling and angiogenesis in a postmenopausal osteoporosis mouse model

Abstract: Osteoporosis is a major health problem, making bones fragile and susceptible to fracture. Previous works showed that mechanical loading stimulated bone formation and accelerated fracture healing. Focusing on the role of Wnt3a (wingless/integrated 3a), this study was aimed to assess effects of mechanical loading to the spine, using ovariectomized (OVX) mice as a model of osteoporosis. Two‐week daily application of this novel loading (4N, 10Hz, 5 min/d) altered bone remodeling with an increase in Wnt3a. Spinal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…In vivo experiments showed that mechanical loading reduces the number of osteoclasts, and molecular experiments revealed that the expression of osteoclast-related factors decreases after mechanical loading. In vitro analysis confirmed that mechanical loading inhibited differentiation, migration, and adhesion of osteoclasts (22,23,40). Our previous study showed that responsiveness to ankle loading differs in the periosteum and endosteum.…”
Section: Discussionsupporting
confidence: 63%
“…In vivo experiments showed that mechanical loading reduces the number of osteoclasts, and molecular experiments revealed that the expression of osteoclast-related factors decreases after mechanical loading. In vitro analysis confirmed that mechanical loading inhibited differentiation, migration, and adhesion of osteoclasts (22,23,40). Our previous study showed that responsiveness to ankle loading differs in the periosteum and endosteum.…”
Section: Discussionsupporting
confidence: 63%
“…The ratio between length of TRAP-positive cells and total circumference of bone trabecula was calculated. 23 It represented the activity of osteoclast. MacNeal's staining was used for identifying osteoblasts as described previously.…”
Section: Histology Trap Macneal's and Immunohistochemistry Assaysmentioning
confidence: 99%
“…Javaheri et al showed that mice with a heterozygous deletion of β‐catenin in osteocytes lose the ability to form new bone in response to mechanical loading . Furthermore, our previous experiments showed that knee loading could inhibit osteoclast development by regulating Wnt signaling and be used to treat early OA, Wnt3a plays a key role in the treatment of OP in response to knee loading . However, whether knee loading also plays a role in OPOA by regulating Wnt signal is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis was caused by many factors and is characteristic of the decreased bone mineral density (BMD) and the deteriorated microarchitecture of bone and thereby increasing the incidence of fracture (Li et al, 2019). Osteoporosis is divided into two categories: primary osteoporosis and secondary osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a monoclonal antibody against RANKL is proved to be highly effective in blocking bone resorption and leads to development of a drug denosumab that successful reduces fractures, which is now one of the therapeutic options for osteoporosis treatment (Solling, Harslof, & Langdahl, 2018). However, more and more attention has been paid to the abnormalities of bone metabolism and related diseases caused by the activity or differentiation abnormalities of osteoblast (Li et al, 2019; Son, Lee, Lee, Lee, & Oh, 2019). The balance between osteoblast proliferation and apoptosis determines the number of active osteoblasts, thereby affecting bone formation homeostasis.…”
Section: Introductionmentioning
confidence: 99%